225k views
5 votes
Solve the following quadratic-linear system of equations.

Solve the following quadratic-linear system of equations.-example-1
User Mkeremguc
by
5.8k points

1 Answer

3 votes

For this case we have a system of two equations with two unknowns.


To solve, we equate both equations:



2x-2 = x ^ 2-x-6\\x ^ 2-3x-4 = 0

We have a quadratic equation of the form:



x ^ 2 + bx + c = 0

Where:



a = 1\\b = -3\\c = -4

Its roots are given by:



x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}\\x = \frac {- (- 3) \pm \sqrt {(- 3) ^ 2-4 (1) (- 4)}} {2 (1)}\\x = \frac {3 \pm \sqrt {9 + 16}} {2}\\x = \frac {3 \pm \sqrt {25}} {2}\\x = \frac {3 \pm5} {2}\\

We have two roots:



x_ {1} = \frac {3 + 5} {2} = 4\\x_ {2} = \frac {3-5} {2} = - 1

Thus, we look for the values of y, by substituting any of the equations:



For\ x_ {1} = 4,\ y_ {1} = 2 (4) -2 = 6\\For\ x_ {2} = - 1,\ y_ {2} = 2 (-1) -2 = -4

Answer:



(x_ {1}, y_ {1}) = (4,6)\\(x_ {2}, y_ {2}) (- 1, -4)

Option B

User Basaa
by
5.6k points